2001
DOI: 10.1128/iai.69.5.3041-3047.2001
|View full text |Cite
|
Sign up to set email alerts
|

Improved Immunogenicity and Protective Efficacy of a Tuberculosis DNA Vaccine Encoding Ag85 by Protein Boosting

Abstract: C57BL/6 mice were vaccinated with plasmid DNA encoding Ag85 from Mycobacterium tuberculosis, with Ag85 protein in adjuvant, or with a combined DNA prime-protein boost regimen. While DNA immunization, as previously described, induced robust Th1-type cytokine responses, protein-in-adjuvant vaccination elicited very poor cytokine responses, which were 10-fold lower than those observed with DNA immunization alone. Injection of Ag85 DNA-primed mice with 30 to 100 g of purified Ag85 protein in adjuvant increased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
184
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(201 citation statements)
references
References 39 publications
13
184
1
3
Order By: Relevance
“…Therefore, various approaches were tested that sought to take advantage of combining the ability of DNA to prime Ab responses with the ability of recombinant proteins to boost them. DNA-protein primeboost regimens have been studied extensively in HIV (58), providing partial protection from simian-human immunodeficiency virus challenge (59) and also have been studied in anthrax (60), tuberculosis (61), and in transmission-blocking vaccines for both vivax and falciparium malaria (62).…”
Section: Mixed Modality Vaccinesmentioning
confidence: 99%
“…Therefore, various approaches were tested that sought to take advantage of combining the ability of DNA to prime Ab responses with the ability of recombinant proteins to boost them. DNA-protein primeboost regimens have been studied extensively in HIV (58), providing partial protection from simian-human immunodeficiency virus challenge (59) and also have been studied in anthrax (60), tuberculosis (61), and in transmission-blocking vaccines for both vivax and falciparium malaria (62).…”
Section: Mixed Modality Vaccinesmentioning
confidence: 99%
“…Prophylactic DNA vaccines expressing M. tuberculosis antigens or cytokines are of particular interest, because of their efficiency and long-lasting effect in animal TB models. For example, prophylactic DNA vaccines expressing various M. tuberculosis antigens, including Ag85A, [15][16][17] Ag85B, 17,18 65 kDa heat shock protein, 19,20 and PstS-3 21 , were found to be effective at limiting the growth of M. tuberculosis in mice. In contrast, there has been little evidence that DNA vaccines are useful as therapeutic vaccines against TB.…”
Section: Introductionmentioning
confidence: 99%
“…In prophylactic settings, there are several reports that DNA vaccines expressing M. tuberculosis antigens are effective for limiting the bacterial growth in mice. [10][11][12][13] However, it is still controversial whether DNA vaccines work against TB reactivation in postexposure models. [14][15][16] For example, the vaccination of plasmid DNA expressing hsp65 after completion of chemotherapy was shown to be effective in preventing the reactivation of intravenously infected M. tuberculosis.…”
mentioning
confidence: 99%
“…Firstly, it has been reported that the Ag85A epitopes are frequently expressed on the surface of the infected macrophages during early phase, but downregulated at the late phase, while PstS-3-specific epitopes are more abundantly expressed during late phase. 13 Thus, DNA immunization with combination of these two genes might induce both Ag85A-and PstS-3-specific immune responses required for suppressing bacterial growth during both early and late phases. Secondly, it has also been known that CD4 + T cells play an important role in the protection for the acute Figure 2 Preventive effect of DNA vaccines given during chemotherapy on reinfection of M. tuberculosis.…”
mentioning
confidence: 99%